PENGARUH MODEL GROUP INVESTIGATION TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN GUGUS I PONTIANAK SELATAN - Wahyuni, Endang Sri; Kartono, Kartono; Syamsiati, Syamsiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to analyze the influence of cooperative learning model of group investigation on the learning outcomes of natural science students of class V State Elementary School I Gugus I Pontianak Selatan. The method used is experimental method, in the form of quasi experimental and type of Nonequivalent Control Group Design. The study population is all the students of grade V of State Elementary School of Gugus I Pontianak Selatan is accreditation B which amounts to 142 students. The sample of this research is all students of class V State Elementary School 12 Pontianak Selatan which amounts to 48 students. The result of this research shows that there is influence of cooperative learning model of group investigation toward the learning result of natural science student of class V of State Elementary School of Gugus I Pontianak Selatan as evidenced by the result of t-test of student post-test data that is tcount ≥ ttable or 2,307 ≥ 1,714 means there are significant differences. The effect of the influence of cooperative learning model of group investigation on the results of natural science learning using the effect size and produce 0,58 are classified as being. Keywords: Cooperative Learning, Group Investigation,Learning Outcomes